TEORI PENDIDIKAN HUMANISTIK DAN IMPELEMENTASINYA DALAM PROSES PEMBELAJARAN - Jacobus, Susan N.H; Lumapow, Harol R.; Pangalo, Lady (JAMBURA Elementary Education Journal, 2023)
Learning should help people become more like themselves, says humanistic thinking.Assuming the learner has a firm grasp on both himself and his immediate surroundings, we may say that the learning process has been fruitful. Put another way, pupils are able to reach their full potential as individuals. Among the numerous advantages of incorporating humanistic approaches into equitable learning are the following: the cultivation of a more complete person, a more developed conscience, a shift in societal attitudes and phenomena, the establishment of routines that are more democratic, participatory, dialogic, and human, the promotion of an atmosphere of mutual respect in the classroom, the promotion of free speech, and the submission of ideas. Reading, taking notes, and organizing research resources are all part of library research, which is a way of gathering library data. Learning within the context of humanistic philosophy, this study's findings support the premise that students perform better academically when they are emotionally and psychologically well-supported. It also confirms that students develop greater resilience and self-assurance when they are more comfortable opening up about their thoughts, feelings, values, expectations, and aspirations. Personality and conscience development, attitude and thought shifts, examination of social phenomena, democratic and participatory learning, interactive and human nurturing are just a few of the many advantages of using humanistic methods to equitable learning.